Current Trends and New Approches for IP Education Training and Research: (Indonesian Perspective) - Sardjono, Agus (UI Scholars Hub, 2008)
Trend in Intellectual Property Rights (IPRs) is mainly influenced by certain situation that attracts public attention. In Indonesia, Trend is more oriented on the issues regarding to the recognition and protection of genetic resources and traditional knowledge and folklore. Cases such as maize varieties, avian influenza and genetic resources have brought impact and became trend in public discussion. This article is limited to share information about Trend in IPR Education, Training and Research based on the experience in Indonesia.